Teacher Roles in Differentiated Instruction in Elementary IPAS Learning: Peran Guru dalam Pengajaran Berdiferensiasi pada Pembelajaran IPAS di Sekolah Dasar - Adilah Hidayatun Nisaa'ul Ulaa; Mahardika Darmawan Kusuma Wardana (Academia Open, 2025)
General Background: Differentiated instruction has emerged as a key approach for addressing diverse student needs in contemporary elementary education. Specific Background: In Indonesian primary schools implementing the Merdeka Curriculum, classroom teachers are expected to adapt instruction to students’ readiness, interests, and learning profiles, particularly in IPAS subjects emphasizing experiential learning. Knowledge Gap: Despite its importance, empirical understanding of how classroom teachers enact differentiated roles in real classroom contexts remains limited, especially within local elementary settings. Aims: This study analyzes the roles of a classroom teacher in implementing differentiated instruction in a fourth-grade IPAS class at SDN Sidoklumpuk Sidoarjo. Results: Using a qualitative phenomenological approach with interviews, observations, and documentation, the study found that the teacher enacted five key roles: facilitator of learning opportunities, mentor, student reader, provider of learning responsibility, and teacher of learning skills, while differentiating content, process, product, and learning environment based on student characteristics. Novelty: The findings demonstrate adaptive and reflective enactment of all five roles within an authentic Indonesian classroom context. Implications: These results provide practical insights for teachers and schools seeking to implement student-centered differentiated iHighlights: Five pedagogical functions were consistently enacted according to Tomlinson’s framework. Instructional adjustments addressed readiness, interests, and learning profiles across multiple dimensions. Classroom practices fostered meaningful, student-centered learning experiences in a real school context. Keywords: Differentiated Instruction; Teacher Roles; Elementary Education; IPAS Learning; Qualitative Phenomenology